A proposed model for using innovative marketing in social media platforms - A field study on Mobily customers, Saudi Arabia - Abdullah, Motaz Talat; Al-Salboud, Saad Abdullah (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to know the extent to which Mobily applied innovative marketing in the social communication platforms, and to know the effect of using innovative marketing in the social communication platforms on consumer attitudes. The study sample consisted of 273 of Mobily customers in the KSA, the study used descriptive method of study. After data collection and analysis several results have been reached: Innovative marketing in social networking platforms contributes significantly to determining consumer trends. Mobily applies pioneering marketing in social networking sites well, As the overall average for innovative marketing hub in social media platforms reached 2.384. There is a statistically significant relationship between innovative marketing in social communication platforms and consumer trends at a significance level (0.05). Based on the results of the study, the researcher presented a number of recommendations, the most important of which is: the need for companies to adopt the means of social communication in their work and focus their efforts in increasing the effectiveness of their content on the networks. Formation of Companies Teams is responsible for following up, developing and updating their content on the means of social communication and follow-up responses of users of their content. Encourage users of social media to adhere to the credibility of information about products and services published on their personal accounts.
Keywords: marketing; innovative marketing; customer trends; social media platforms; cognitive component